Establishment of a Clone of Mouse Hypothalamic Neurosecretory Cells Synthesizing Neurophysin and Vasopressin - Vitry, F. De (1974)
Hypothalamic cells taken from 14-day-old mouse embryos were cultured for 6 days and transformed with simian virus 40. After cloning, a homogeneous cell population was obtained. Its morphological, Ultrastructural, biochemical, and immunochemical properties were studied. These cells possess ultrastructural features of primitive neurosecretory cells. They synthesize (35)S-labeled protein components that have the molecular weight and isoelectric focusing behavior of, and display the same immunoreactivity as, neurophysin. In addition, a (35)S-labeled peptidic fraction with a molecular weight close to 1000 is synthesized and is radioimmunologically indistinguishable from vasopressin. Immunochemical staining shows that both neurophysin and vasopressin are localized in the cytoplasm. These observations strongly suggest that a clone of mouse hypothalamic neurosecretory cells has been obtained with the synthesizing capacities of secretory neurons of the magnocellular hypothalamic nuclei.